ON THE MAGNETIC VARIABILITY OF PULSATING STARS - Udovichenko, S. N.; Romanov, Yu. S.; Frolov, M. S. (Одеські астрономічні публікації, 2017)
The variations of the effective magnetic field strength of the magnetic stars a 2 CVn, b CrB and of the pulsating stars RR Lyr and V 474 Mon are studied on the base of the spectrograms obtained at the 6-m telescope. The variation with the phase of the 0d.567 pulsating period was found in R Lyr. Our results together with the Babcock‘s observations in the 1950s show that the mean field depends on the phase of the 40d.19 Blazhko period, presumably because the rotational and the magnetic axes are not coinciding. For V 474 Mon, is not possible to clear up the character of such Variation.